WOMEN’S LANGUAGE USED BY FEMALE CHARACTERS IN WONDER WOMAN MOVIE - Septiari, Ni Luh Putu Eka; Sedeng, I Nyoman; Beratha, Luh Sutjiati (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTIt aimed at identifying the language features applied by female characters and finding outthe functions of each type of women’s linguistic features. This paper used the theory ofwomen’s linguistic features proposed by Lakoff. She describes ten women’s languagefeatures: lexical hedges, tag questions, rising intonation on declarative, empty adjectives,precise colour terms, intensifiers, hypercorrect grammar, super polite forms, avoidanceof strong swear words, and emphatic stress. The data source in this study is WonderWoman Movie. The movie was chosen as the data source because it contained manywomen’s dialogues and the features and function of women’s language. The collecteddata was identified and selected, then analyzed the features of women’s language used bythe female characters in Wonder Woman movie and analyzed the function of women’slinguistic features based on Lakoff. The method applied in collecting data was thedocumentation method. Afterwards, the method of analyzing data in this study was thedescriptive qualitative method. This study applied the informal method in presenting thedata analysis, which represented the result of analysis by using words and its purposes togive the explanation to make the readers understand easily. The findings of the analysisshowed there were six kinds of women’s linguistic features found in Wonder WomanMovie: lexical hedges or fillers, rising intonation on declarative, empty adjectives,hypercorrect grammar, super polite form, and intensive adverbs. There were also somefunctions of women’s linguistic features found in the data. The functions of each type offeature are closely related to the context in which it is used. Each type of women’slinguistic feature found in the movie displays has different functions and reasons. Ingeneral, the finding of the analysis of functions aimed to be polite and avoiding strongexpressions.Keywords: Women’s Language, Female Characters, Wonder Woman Movie.ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi ciri kebahasaan yang diterapkan olehtokoh perempuan dan mengetahui fungsi masing-masing jenis ciri kebahasaanperempuan. Makalah ini menggunakan teori fitur linguistik perempuan yangdikemukakan oleh Lakoff. Dia menjelaskan sepuluh fitur bahasa wanita: batasan leksikal,pertanyaan tag, intonasi naik pada deklaratif, kata sifat kosong, istilah warna yang tepat,intensifiers, tata bahasa hiperkoreksi, bentuk super sopan, menghindari kata-kataumpatan yang kuat, dan tekanan empatik. Sumber data dalam penelitian ini adalahWonder Woman Movie. Film tersebut dipilih sebagai sumber data karena banyak memuatdialog-dialog perempuan serta fitur dan fungsi bahasa perempuan. Data yang terkumpuldiidentifikasi dan diseleksi, kemudian dianalisis fitur bahasa wanita yang digunakan oleh karakter wanita dalam film Wonder Woman dan menganalisis fungsi fitur linguistikwanita berdasarkan Lakoff. Metode yang digunakan dalam pengumpulan data adalahmetode dokumentasi. Selanjutnya, metode analisis data dalam penelitian ini adalahmetode deskriptif kualitatif. Penelitian ini menerapkan metode informal dalammenyajikan analisis data, yang merepresentasikan hasil analisis dengan menggunakankata-kata dan tujuannya untuk memberikan penjelasan agar mudah dipahami olehpembaca. Temuan analisis menunjukkan ada enam jenis fitur linguistik wanita yangditemukan di Wonder Woman Movie: leksikal hedges atau pengisi, intonasi naik padadeklaratif, kata sifat kosong, tata bahasa hiperkoreksi, bentuk super sopan, dan kataketerangan intensif. Ada juga beberapa fungsi fitur linguistik perempuan yang ditemukandalam data. Fungsi masing-masing jenis fitur terkait erat dengan kontekspenggunaannya. Setiap jenis fitur kebahasaan perempuan yang terdapat dalam tayanganfilm memiliki fungsi dan alasan yang berbeda-beda. Secara umum, temuan analisis fungsibertujuan untuk bersikap sopan dan menghindari ekspresi yang kuat.Kata kunci: Bahasa Wanita, Karakter Wanita, Film Wonder Woman.